A multilevel investigation of cultural competence among South Korean clinical nurses. Issue 3 (15th October 2019) - Chae, Duckhee; Park, Yunhee; Kang, Kyeonghwa; Kim, Jongdae
Abstract : Background: There is lack of empirical evidence on whether organisational variables affect the cultural competence of nurses. Aim: This study aimed to investigate individual and organisational characteristics associated with South Korean clinical nurses' cultural competence. Methods: A descriptive cross‐sectional research design was used. A convenient sample of 401 clinical nurses from 21 hospitals in South Korea was recruited between November 2015 and February 2016. Multilevel modelling was used to estimate the effects of individual‐ and organisation‐level predictors. Data were analysed using the nlme package in R. Results: Multilevel modelling indicated that professionalism (β = 0.02, p < 0.001) and foreign language fluency (β = 0.25, p = 0.012) were significant individual‐level predictors. Education on foreign patient care was marginally significant at p = 0.069. At the organisational level, nurse‐to‐patient ratio (β = 0.37, p = 0.038) and organisational cultural competence (β = 0.02, p < 0.001) were significant predictors. In addition, hospital ownership and work environment were marginally significant at p = 0.054 and p = 0.050, respectively. Furthermore, there was a significant cross‐level interaction between professionalism and hospital ownership (β = 0.03, p = 0.003). Conclusion: To provide culturally competent care, nurse leaders should recognise the importance of organisational‐level factors, such as nurse staffing and organisational cultural competence, and create an environment that is inclusive of diverse patients, as well as promote professionalism among individual nurses.